Диета для трех поросят: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2009)
Экземпляры: аб. ЦБ (20200917) / Инвентарный номер: 9775 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6